DINAMIKA EKONOMI POLITIK INDUSTRI PENERBITAN PERS LOKAL (Studi Kasus Praktek Komodifikasi dan Spasialisasi di Kota Kupang) - , Yoseph Andreas Gual, Prof. Y. A Nunung Prajarto ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research comes from the reality of local daily news life in Kupang city, East Nusa Tenggara Province that conform to the alteration of social politic in Indonesia. Kupang City has only one local news in the era Orde Baru but since the reformation surround Indonesia has been born 12 local news in Kupang. In the period of time, in 2013 remain 5 local newspaper. Tree of them has protected by the national newspaper and the two other protected by local people-the first of three local newspaper growth well and dominated NTT while two other were floated. In field of communication, this situation make a little problem with the recitation of economic political media. Therefore, the question is used to research how is applied to the (economic) political media especially modification and spacialization for the daily local media, Pos Kupang,Timor Express, Erende Pos and Radar Timor can be competed among them. The aim of the research is to explain modification and specialization in order to find reason as background for the fourth media to applied them. This research use paradigm of constructivisme with case study method. The researcher discovered that the fourth local media applied the modification and specialization practically with different ways. The modification in content, audience and worker is done by 2 local media which is protected by national media regard success and become the endorsement for both media to survive and to expand. Practically modification is more professional that impressed without deceit. This happened because both local media is supported by media corporation which protect them. While two other local media which is not agree with media corporation to apllied practical modification with limit knowledge of the owner not based on the business media modern consideration. This made Erende Pos difficult to compete with Pos Kupang, Timor Express and Radar Timor collapses. From spacialization side the forth media try hard to do but from the owner side, the main stock of two media belongs to national media corporation. Pos Kupang and Timor Express is the result of spacialization of each main corporation. With the supported by the main media corporation, both local media can be improve and expand, its vertically and horizontally. On the contrary, tho other media try to do spasialization buf fail. Erende Pos that have the same institution with Nusa Lontar University in Rote Island try to make long distant Printed and it is a plan. While Radar Timor is one of local news paper can not be stand and its also collapses. From the data above can be that practical modification and spacialization has been done the forth local media not only for surviving but also to improve it more progress. Mean while the destiny of the fourth local media have different way on the pratical commodification and spacialization. Both of the frourth local media which protected by the national media corporation can be exist now as daily newspaper in NTT. It supported by the main media corporation of each daily news paper whether its material, organizer, management and human resource. With this financial capital, two local media can run business professional destroy the jurnalistic itsel because of the entering personal dizziness to get more profit. With the sufficient capital, Pos Kupang and Timor Express is also can be expand two other business which make them receipt by the society in NTT. The two other business is social financial and political financial. With this, their progress to many resources will be broad, public receipt, and their advertisement will be increase. What happened to Erende Pos and Radar Timor. They learn to run their business by themselves, work for themselves without endorsement from other. This make them unknown by the people, bad journalistic and their business tend to the far from professional work.